Can GDPR and Copyright law stop deepfake? A comprehensive legal analysis of the deepfake phenomenon and liability for the deepfake in the polish legal system - Wróbel, Agata ("Młody Jurysta" Czasopismo Studentów i Doktorantów Wydziału Prawa i Administracji UKSW, 2024)
The article is a comprehensive analysis of the relationship between deepfake technology and identity issues in the context of the Polish legal system. In the context of the dynamic development of generative Artificial Intelligence systems, an important aspect is the protection of individuals' identities. This article focuses on two key areas: detection technology and the legal framework that balances freedom of speech with the protection of identity and information security. The first part of the article focuses on the role of detection technology in combating deepfake. Current trends and advances in the field of content manipulation are analyzed. The second important aspect addressed in the article is the analysis of the legal framework regulating deepfake in Poland. Criminal and civil liability issues related to the creation and dissemination of deepfake are discussed, with a particular focus on image protection and related copyright law an related rights. The relationship between creative freedom and the protection of individual identity is also analyzed, including through the lens of Polish case law. The last part of the article focuses on current developments in the European AI Act (status as of December 2023). It is indicated how the new AI regulations affect the issues of identity protection and combating deepfake.